MINAT MASYARAKAT MEMILIH PEMBIAYAAN DI PNM MEKAR SYARIAH CABANG KRONJO KABUPATEN TANGERANG MENURUT PERSPEKTIF EKONOMI ISLAM - Afifah Nazla Sevina; Suryani; Ratu Humaemah (Wahana Islamika Jurnal Studi Keislaman, 2022)
Many people in Kronjo Tangerang Regency, have become customers at PNM Mekar Syariah as an effort to increase their business capital. This is evidenced by the increasing number of customers of PNM Mekar Syariah Branch Kronjo Tangerang Regency from year to year. The purpose of this study is to find out the factors that influence public interest in choosing financing at PNM Mekar Syariah. The method used in this research is descriptive qualitative research. The data sources used are primary data sources and secondary data sources. The data was obtained using the triangulation technique of data sources, by combining data collection with observation techniques, structured interviews and documentation. The results of this study indicate that the public's view of financing at PNM Mekar Syariah Kronjo Branch, Tangerang Regency is good and helps people who need capital to run their business or want to open a business but do not have capital. PNM Mekar Syariah Branch Kronjo in its financing system uses sharia principles and has three contracts used, namely wadi'ah contracts, wakalah contracts and murabahah contracts. The factors that influence people's interest in choosing financing are the need factor, religiosity factor, social class factor and service quality.